Book-Tax Differences as an Indicator of Earnings Quality: A Study of Tax Accounting Literature - Ratna Dina; Sri Handayani; Lidya Christine Wattileo (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This study aims to systematically examine the role of Tax-Book Differences (BTD) as an indicator of earnings quality and a detection tool for earnings manipulation practices from a tax accounting perspective. This research uses a Systematic Literature Review (SLR) approach with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines on scientific articles of national and international repute published in the period 2015-2024. From a systematic selection process, 12 key articles were thematically synthesised. The results show that BTD not only reflects technical differences between accounting standards and tax regulations, but also contains information about management's discretionary and opportunistic behaviour. BTD, especially those that are abnormal in nature, are shown to be associated with reduced earnings quality characterised by low earnings persistence and increased information uncertainty. The decline in earnings quality further increases the tendency of earnings manipulation practices, both through discretionary accounting policies and real activity manipulation. This study develops a conceptual framework that integrates the direct and indirect relationships between BTD, earnings quality, and earnings manipulation, and confirms the role of earnings quality as the main transmission mechanism. The research findings provide conceptual contributions to the development of tax accounting literature and practical implications for regulators in utilising BTD as an indicator of risk-based supervision, particularly in the Indonesian context.